FEATURES PRICING OF THE WORLD MARKET OF DIESEL FUEL - I. Davydov (Вестник университета)
The price of diesel fuel is influenced by various factors that identity this product as a separate commodity market. The article analyzes the specifics of prices on the world market of diesel fuel, discussed in detail the various components of the price, as well as described methods of state regulation of prices for diesel fuel.